Three-dimensional vibration analysis of fluid-filled pipes - Kolo, Isa; Idres, Moumen; Kafafy, Raed; Shaik Dawood, Mohd. Sultan Ibrahim (2013)
A numerical model based on one-dimensional wave theory incorporating Poisson and junction coupling is used to carry out three-dimensional vibration analysis of a straight pipe filled with fluid. The Transfer Matrix Method is used to represent the fluid and structural vibration equations in the frequency domain. The natural frequencies of the pipe in fluid and structural modes are determined for various end conditions. Hydraulic excitation is considered to obtain pressure frequency response. Results obtained compared well with available analytical solutions and ANSYS software results.